Professional Difficulties Faced by Young Teachers in Municipal Education Organizations - Irina V. Davydova; Tatyana N. Semenkova (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Successful professional adaptation of young teachers is a state policy aimed at unifying academic environment, achieving national independence, and prioritizing the role of qualified teaching staff. The education system seeks to overcome teaching personnel shortage on the municipal level by supporting young teachers in the first years of work and encouraging them to stay in the profession and develop their professional skills. The article introduces a sociological study of professional difficulties, based on a self-assessment survey of young teachers employed in general education organizations of Kemerovo, Russia. The research results revealed the current and most urgent professional difficulties experienced by local young teachers. They provided the municipal education system with complete, objective, and up-to-date information for a more effective scientific and methodological support in the sphere of continuous education and professional adaptation of young teachers. The most serious difficulties faced by young teachers were associated with methodological documentation, communication with parents, and crises of life strategies. The major professional deficiencies in subject, methodological, and communicative competencies usually correlated with the poor professional and life experience. The research results can improve the system of professional adaptation support and development for young teachers in the region, as well as to expand the information field for making managerial decisions.